2008
DOI: 10.1021/ma801492a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled/Living Cyclopolymerization of tert-Butyl α-(Hydroxymethyl) Acrylate Ether Dimer via Reversible Addition Fragmentation Chain Transfer Polymerization

Abstract: Reversible addition fragmentation chain transfer (RAFT) polymerization was used in the cyclopolymerization of a symmetrical difunctional monomer, tert-butyl α-(hydroxymethyl)acrylate ether dimer. Cumyl dithiobenzoate (CDB) was chosen as the RAFT agent and N,N′-azobis(isobutyronitrile) (AIBN) was employed as the initiator. Polymerizations were carried out in xylene at 70 °C. Under tuned conditions, cyclic soluble polymers with six-membered tetrahydropyran repeat units were obtained. Polydispersities of the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
(77 reference statements)
1
28
0
Order By: Relevance
“…Higher concentrations of AIBN at constant cumyl dithiobenzoate and monomer concentrations resulted in higher PDIs (see Table S1 in the Supporting Information) and deviation from theoretical molecular weights, similarly to previous reports. [13] As it is important to efficiently target samples of variable molecular weights with narrow PDIs, thus using also relatively low amounts of RAFT initiator, several other solvents were tested, with 1,4-dioxane giving the best results (Table 3). If at 80 8C, good conversions, PDIs and agreement between observed and calculated M n were observed, by lowering the temperature to 70 8C, results were further improved, especially in terms of PDI values at either a low or high percentage of RAFT reagents (entry 3 and entry 4, Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher concentrations of AIBN at constant cumyl dithiobenzoate and monomer concentrations resulted in higher PDIs (see Table S1 in the Supporting Information) and deviation from theoretical molecular weights, similarly to previous reports. [13] As it is important to efficiently target samples of variable molecular weights with narrow PDIs, thus using also relatively low amounts of RAFT initiator, several other solvents were tested, with 1,4-dioxane giving the best results (Table 3). If at 80 8C, good conversions, PDIs and agreement between observed and calculated M n were observed, by lowering the temperature to 70 8C, results were further improved, especially in terms of PDI values at either a low or high percentage of RAFT reagents (entry 3 and entry 4, Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…[27][28] Reports on the successful application of ATRP [11] and RAFT [12][13][14][15] methof the article's abstract page, which can be accessed from the journal's homepage at http://www.mcp-journal.de, or from the author.…”
Section: Introductionmentioning
confidence: 99%
“…[375] However, Lee et al [176] found disulfide formation to be significant during the hydrazinolysis of St/AcS copolymers. DADMAC [113,440] N Cl Ϫ 427 [589] O OC(CH 3 ) 3 OC(CH 3 ) 3 O O 428 [590] O O O O 429 [590] O O O O n 430 [591] O O…”
Section: Radical-induced Oxidationmentioning
confidence: 99%
“…In recent years, controlled radical polymerizations have been used for the formation of rigid cyclolinear polymers of well‐defined size and interesting structural properties 8–13. For example, some of the cyclolinear polymers bore particularly large cycles of 10‐ to 19‐membered rings 11–13.…”
Section: Introductionmentioning
confidence: 99%
“…In another case, the polymers prepared bore positive charge; this was the work by Agarwal and coworkers8 who reported the use of reversible addition–fragmentation chain transfer (RAFT) cyclopolymerization of alkyl ammonium dienes to synthesize cyclolinear polymers with five‐membered heterocyclic monomer repeating units. Conversely, Acar and coworkers9, 10 used atom transfer radical cyclopolymerization and RAFT cyclopolymerization of the tertiary ‐butyl α‐(hydroxymethyl)acrylate (TBHMA) ether dimer for the preparation of homopolymers and copolymers with six‐membered heterocyclic monomer repeating units. Although the tertiary ‐butyl group in the TBHMA ether dimer units could be readily hydrolyzed to convert these cyclolinear polymers to rigid polyanions, this was not attempted.…”
Section: Introductionmentioning
confidence: 99%